1996
DOI: 10.1097/00004647-199603000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metabolism of Patients with Stenosis of the Internal Carotid Artery before and after Endarterectomy

Abstract: Occlusion or severe stenosis, with a reduction in the diameter of more than 70% of the extracranial arteries may lead to hpoperfusion of the brain with an increased risk of cerebral infarction. The aim of this study was to investigate whether endarterectomy of stenosed internal carotid arteries leads to alternations in cerebral metabolism in regions in which no infarcts were visible with magnetic resonance imaging (MRI). We studied 10 healthy control subjects and 20 patients with transient or nondisabling cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…While most of these studies reported increases in these values after CEA, [23][24][25][26] the remainder found no changes. 30 The variation in results between these studies may be from differences in methodologic factors, including the number of patients, types of patient, types of MR scanners, and the timing of postoperative assessment. In particular, previous studies have been performed by using devices operating at 1.5T and included a relatively smaller sample size (Յ20 subjects).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of these studies reported increases in these values after CEA, [23][24][25][26] the remainder found no changes. 30 The variation in results between these studies may be from differences in methodologic factors, including the number of patients, types of patient, types of MR scanners, and the timing of postoperative assessment. In particular, previous studies have been performed by using devices operating at 1.5T and included a relatively smaller sample size (Յ20 subjects).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, previous studies have been performed by using devices operating at 1.5T and included a relatively smaller sample size (Յ20 subjects). [23][24][25][26]30 The main advantages of proton MR spectroscopy at 3T over that at 1.5T include a higher signalto-noise ratio, higher spatial and temporal resolutions, and better spectral resolution. 11 These advantages allow acquisitions of higher quality and result in a higher sensitivity for the detection of nervous system metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…NAA is found exclusively in mature neurons and neuronal processes (3,4). Several studies have demonstrated that an area of brain with relative reduction of NAA correlates with either neuronal loss (5-1 2,13-18) or dysfunction (12,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) compounds (Cho) and creatine-and phosphocreatinecontaining compounds (Cr), seen at 3.2 and 3.0 ppm, respectively (1,2). Cr, a metabolite important for energy metabolism, is found in neurons and glia cells, and is relatively homogeneously distributed throughout the normal brain (29-31).…”
mentioning
confidence: 99%
“…12,13 In addition to assessment of the presence and extent of infarcts with MRI, MR angiography (MRA) can be applied to quantify flow in the middle cerebral arteries (MCAs), 14 and 1 H MR spectroscopy (MRS) has proven to be a valuable tool to study metabolic changes in the brain in both infarcted 15,16 and noninfarcted areas. 17, 18 The purpose of this study was to assess whether MR can provide prognostic information about the recurrence of cerebral ischemic events in patients with symptomatic CAO. We investigated the prognostic value of 3 factors that on theoretical grounds 12,19 may be related to the blood flow state of the brain: (1) presence of a relevant infarct of the border-zone type; (2) quantitative flow in the MCA ipsilateral to the symptomatic CAO; and (3) metabolic ratios measured by 1 H MRS, ipsilateral to the symptomatic CAO.…”
mentioning
confidence: 99%